2014
DOI: 10.1227/neu.0000000000000127
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Diminished Olfactory Sensation After Treatment of Bilateral Ophthalmic Segment Aneurysms With Flow Diversion

Abstract: Intracranial aneurysms causing dysfunction of olfactory sensation due to mass effect upon the olfactory tract can be successfully treated with flow diversion. Flow diversion should be considered as one of the treatment options for patients with cranial nerve dysfunction due to unruptured intracranial aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Thus, ACA, ACOM, and OA aneurysm locations display an anatomic risk factor potentially hampering olfactory function due to thromboembolic ischemic events or neurovascular compression (Hendrix et al, ). Kelkar et al () reported a case of bilateral ophthalmic aneurysms causing hyposmia which moderately improved after bilateral flow diversion and consequent aneurysm occlusion. Manconi et al () and Ito et al () have reported a case of a giant ACOM aneurysm associated with olfactory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ACA, ACOM, and OA aneurysm locations display an anatomic risk factor potentially hampering olfactory function due to thromboembolic ischemic events or neurovascular compression (Hendrix et al, ). Kelkar et al () reported a case of bilateral ophthalmic aneurysms causing hyposmia which moderately improved after bilateral flow diversion and consequent aneurysm occlusion. Manconi et al () and Ito et al () have reported a case of a giant ACOM aneurysm associated with olfactory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial aneurysms or neoplasms of the anterior cranial fossa may exhibit local mass effect on the arteries that supply the olfactory bulb and olfactory tract. In a recent case report a patient suffering from hyposmia and bilateral ophthalmic segment aneurysms experienced gradual resolution of his inability to smell after endovascular treatment of these aneurysms (Kelkar et al, ). While subarachnoid hemorrhage itself may be a risk factor for anosmia, potentially due to vasospasm in the arteries that supply olfactory structures, the treatment of aneurysms carries an even higher risk.…”
Section: Olfactory Nerve (Cn I)mentioning
confidence: 99%